Review of the Alompra ferruginea Moore, 1872 complex with description of a new species from Taiwan (Lepidoptera, Lasiocampidae) - Wu, Shipher; Lee, Hsueh; Zolotuhin, Vadim V. (Zootaxa, 2017)
The present study reviews the Alompra ferruginea Moore, 1872 group. A. ferruginea bidiensis Tams, 1953 (TL: Borneo) and A. ferruginea cerastes Tams, 1953 (TL: Mindanao) are both raised to bona species level. The population of Taiwan is described as a new species, A. yibinfani sp. nov. The lectotype of A. ferruginea is designated from BMNH, the holotype of A. ferruginea cerastes is designated from USNM. A. ferruginea is listed here from Vietnam for the first time.